Levels of occupational stress and stressful activities for nurses working in emergency - José Ricardo Ferreira da Fonseca; David Lopes Neto (Universidade Federal do Ceará, 2014)
The study aimed to identify stress levels, areas and their activities identified as stressful by nurses working in the emergence in Manaus, AM, Brazil. It is an epidemiological, cross-sectional design, with 36 emergency nurses from December 2010 to January 2011. The Bianchi Stress Scale with 57 questions was used. The nurses were at risk for high levels of stress. The most stressful areas were the operation of the unit, conditions of work and personnel administration, and the most stressful activity was the request for equipment review and repair. The difference by Friedman test between the areas was significant (p <0.05), Dunn post-test significant (p <0.05) when compared by peers. The accumulation of management activities with the assistance activities can generate higher levels of stress, it is necessary to invest in improving the work environment and management support to minimize the stress experienced at work.